2013
DOI: 10.1590/s1517-83822013000200015
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem and cefoxitin resistance of Klebsiella pneumoniae strains associated with porin OmpK36 loss and DHA-1 β-lactamase production

Abstract: Clinical isolates of carbapenem-resistant Klebsiella pneumoniae (K. pneumoniae) strains are being increased worldwide. Five pan-resistant K. pneumoniae strains have been isolated from respiratory and ICU wards in a Chinese hospital, and reveal strong resistance to all β-lactams, fluoroquinolones and aminoglycosides. Totally 27 β-lactamase genes and 2 membrane pore protein (porin) genes in 5 K. pneumoniae strains were screened by polymerase chain reaction (PCR). The results indicated that all of 5 K. pneumoniae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 25 publications
5
42
1
Order By: Relevance
“…Although CMY is the most common type of AmpC β-lactamase in the world, the DHA-1 and ACT types predominate in China (31). In the present study, the DHA-1 type was verified through genotype analysis of AmpC β-lactamase in Klebsiella pneumoniae, which was in accordance with a previous study (32); therefore, DHA-1 AmpC β-lactamase is speculated to be the main genotype in China.…”
supporting
confidence: 91%
“…Although CMY is the most common type of AmpC β-lactamase in the world, the DHA-1 and ACT types predominate in China (31). In the present study, the DHA-1 type was verified through genotype analysis of AmpC β-lactamase in Klebsiella pneumoniae, which was in accordance with a previous study (32); therefore, DHA-1 AmpC β-lactamase is speculated to be the main genotype in China.…”
supporting
confidence: 91%
“…So far, few studies have reported the effect of efflux pump on carbapenems resistance in Enterobacter spp. [55][56][57] The current study showed that the efflux pump inhibitor CCCP was not able to restore the susceptibility of carbapenem-resistant E. coli, indicating that efflux pump was not involved in the carbapenem resistance in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Furthermore, these mechanisms are encoded in mobile genetic elements that can be readily spread intra-and interspecies (8). Additionally, the loss of outer membrane porins (OMPs) further contributes to the varied resistance mechanisms harbored by this pathogen (9,10). Clinically available ␤-lactamase inhibitors (BLIs), such as clavulanic acid, tazobactam, sulbactam, avibactam, and vaborbactam (formerly RPX-7009), have no inhibitory activity against MBL enzymes (11)(12)(13).…”
mentioning
confidence: 99%